Large scale experimental study on the fire hazard of buildings’ U-shape façade wall geometry - Yan, Weigang; Jiang, Lin; An, Weiguang; Zhou, Yang; Sun, Jinhua (Journal of Civil Engineering and Management, 2017)
Buildings have U-shape façade designs for certain purposes such as lighting. However, such designs may lead to a higher fire hazard. In this paper, large scale experiments of upward flame spread over XPS insulation material were conducted to investigate the fire hazard of building’s U-shape façade wall geometry. Comparison to previous laboratory scale experiments were also presented. Theoretical analysis was performed to reveal the mechanism of the U-shape geometry’s influences. It is found that such geometry design would increase the fire hazard of buildings: flame spread rate and flame height increased with U-shape’s geometrical factor. The results agreed with theoretical analysis. It is expected that the buildings’ U-shape façade wall geometry would greatly benefit flame spread for full scale applications and increase the fire hazard. Thus engineers should be careful with such façade wall designs, especially for residential building designs.